Securitising an international humanitarian crisis: news framing of the Syrian refugee crisis in the US. Issue 2 (3rd July 2021) - Jahng, Mi Rosie; Doshi, Marissa J.
ABSTRACT: This study examined how the 2016 Syrian refugee crisis was framed in by US news outlets. Upon applying the concept of securitisation to framing theory, the results from a content analysis indicate that the majority of US news coverage framed Syrian refugees as a nonmilitary issue, emphasising the humanitarian nature of the refugee crisis, as well as a threat to the national security and identity of the US by emphasising terrorism. Implications for news coverage of international conflicts are discussed within the context of framing and securitisation theory.